PELATIHAN PEMANFAATAN WIZER.ME SEBAGAI MEDIA PEMBELAJARAN DIGITAL - Ni Ketut Erawati Ni Ketut Erawati; Ni Kadek Rini Purwati Ni Kadek Rini Purwati; Ni Wayan Suardiati Putri Ni Wayan Suardiati Putri; I Wayan Gede Wardika (ASOSIASI IDEBAHASA KEPRI, 2023)
Digital learning media is a very important learning tool in the blended learning model. The blended learning learning model is a learning model that can be used by teachers to facilitate the learning process because material can be provided in advance through digital learning media. One of the mathematics learning media that can be called digital learning media is the use of wizer.me. Therefore, as a form of lecturer concern in helping teachers develop their abilities and skills in utilizing digital learning media, community service activities are carried out in the form of training on the use of wizer.me as a digital learning medium. The training activities carried out at SD N 6 Ketewel were in the form of introduction and training as well as wizar.me mentoring. Teachers quickly receive digital learning media training materials and can operate or design digital learning media, so that training provides positive feedback. Therefore, this training activity is expected to become an ongoing activity to improve teacher abilities, especially in designing digital learning media. As well as disseminating the teacher's desire to practice the skills they have in developing digital learning media to other schools.